HEART RATE VARIABILITY ANALYSIS - Magrupov, T.M.; Isaev , Kh.A. (Educational Research in Universal Sciences, 2023)
The analysis of heart rate variability (HRV) is a rapidly developing branch of cardiology, in which the possibilities of computational methods are most fully realized. This direction was largely initiated by the pioneering work of the famous Russian researcher R.M. Baevsky [2] in the field of space medicine, who for the first time introduced into practice a number of complex indicators characterizing the functioning of various regulatory systems of the body.